2021
DOI: 10.21203/rs.3.rs-779549/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Delta Variant Predominant at a Tertiary-Care Hospital in Saudi Arabia

Abstract: Despite the effectiveness of the Pfizer-BioNTech and Oxford-AstraZeneca vaccines against SARS-CoV-2, the delta (B.1.617.2) variant of concern (VOC) has spread globally, and breakthrough infections have been reported. We identified the circulating variants and effectiveness of those vaccines between April and June 2021 at a tertiary-care hospital in Saudi Arabia. Among 320 patients with confirmed COVID-19 (mean age, 39 years; 53.6% male), 70.6% received a one-dose vaccination; 15.1% received two-dose vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…Most of the HCWs agreed that the Delta variant could cause a new COVID-19 wave within Saudi Arabia, although the reported cases were still limited at the time of our study [7]. This could represent the knowledge of the HCWs of the rapidly evolution of the Delta variant globally, as the COVID-19 virus is becoming 'fitter and faster' [40].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Most of the HCWs agreed that the Delta variant could cause a new COVID-19 wave within Saudi Arabia, although the reported cases were still limited at the time of our study [7]. This could represent the knowledge of the HCWs of the rapidly evolution of the Delta variant globally, as the COVID-19 virus is becoming 'fitter and faster' [40].…”
Section: Discussionmentioning
confidence: 87%
“…However, there has been growing concern about the level of protection that approved vaccines can provide, as well as the evasion mechanisms. In early May 2021, of 321 patients hospitalized with COVID-19 at a tertiary care center in Riyadh, 131 had the Delta variant [7]. A recent study from Qatar, a neighboring country to KSA, showed an accelerating decline in the effectiveness of BNT162b2 against all variants to 20% five to seven months after the second dose [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, all patients with OI had mild COVID-19, did not require hospitalization, and recovered without complications. Almost half of the patients develop COVID-19 before vaccination or after partial vaccination during the period of circulating SARS-CoV-2 variants of concern, predominately SARS-CoV-2 Delta virus ( 14 ). Nine out of 12 patients were less than 18 years old, 41% were chair bound, and 41% had kyphoscoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since the onset of the coronavirus disease 2019 (COVID-19) pandemic, different variants of the causative virus-the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-have been discovered globally, including the Alpha (B.1.1.7), Beta (B.1.351), and Delta (B.1.617.2) variants. The medical community must further understand their transmission and diagnosis to detect them early and reduce infection by applying the best preventive measures [ 1 ].…”
Section: Introductionmentioning
confidence: 99%